CLINICAL RISK INDEX FOR BABIES (CRIB SCORE) AS A PREDICTOR OF NEONATAL MORTALITY - Zarmast Khan; Nasir Zulﬁqar; Hamid Mahmood et al. (Journal of University Medical & Dental College, 2019)
ABSTRACT:OBJECTIVE: It is very important to predict the outcome among preterm and very low birth weight babies as mortality rates are quite high. CRIB score is used to predict the outcomes in preterm neonates. The objective of this study was to determine the strength of CRIB score in detecting neonatal mortality in babies presenting with very low birth weight.STUDY DESIGN: Cross-sectional study.SUBJECTS: A total of 254 newborns with birth weight of between 500 to 1500 grams and gestational age of ≤35 weeks were included. The study was conducted over a period of 6 months in neonatology department of Shifa International Hospital, Islamabad. METHODS: CRIB score was obtained through a prospective way in all neonates and its association was assessed with mortality during neonatal intensive care unit (NICU) stay. RESULTS: The percentage of male and female newborn subjects was 54.3% (n=138) and 45.7% (n=116) respectively. Mean gestational age was 33.3 weeks ± 1.04 and mean birth weight of study population was 1129.9 grams ± 210.6. Mean CRIB score among the study population was 6.3 ± 3.1 and overall mortality was found to be 54.7% (n=139). Mean CRIB score was found to be 8.27 ± 2.1 among mortality group and it was 3.87 ± 3.4 among newborns who were discharged (P<0.05). Mortality was present in 4.3% (n=4) of neonates with CRIB score between 1-5, 87.1% (n=121) who had CRIB score between 6-10 and 100% (n=14) of neonates who had CRIB score between 1115 (P<0.05).CONCLUSION: Signiﬁcantly higher mortality was noted among neonates with higher CRIB scores.